2010
DOI: 10.1189/jlb.0310154
|View full text |Cite
|
Sign up to set email alerts
|

GM-CSF-induced, bone-marrow-derived dendritic cells can expand natural Tregs and induce adaptive Tregs by different mechanisms

Abstract: In our earlier work, we had shown that GM-CSF treatment of CBA/J mice can suppress ongoing thyroiditis by inducing tolerogenic CD8α(-) DCs, which helped expand and/or induce CD4(+)Foxp3(+) Tregs. To identify the primary cell type that was affected by the GM-CSF treatment and understand the mechanism by which Tregs were induced, we compared the effect of GM-CSF on matured spDCs and BMDC precursors in vitro. Matured spDCs exposed to GM-CSF ex vivo induced only a modest increase in the percentage of Foxp3-express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
93
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(104 citation statements)
references
References 55 publications
9
93
2
Order By: Relevance
“…While it has not been tested if RMA cells or RMA SN increase any of the inhibitory marker expression, these GM-CSF-derived early DCs induce robust T-cell proliferation after LPS stimulation in spite of the pre-existing PD-L1 expression, suggesting that these DCs can induce a strong immune response when given a proper stimulation. This was in line with a study done by Bhattacharya et al [29] where they demonstrated that BM-derived DCs selectively expand regulatory T-cells in the presence of OX40L but not PD-L1. Furthermore, blockade of CD80 on BM-derived DCs has also been shown to discourage regulatory T-cell expansion.…”
Section: Discussionsupporting
confidence: 92%
“…While it has not been tested if RMA cells or RMA SN increase any of the inhibitory marker expression, these GM-CSF-derived early DCs induce robust T-cell proliferation after LPS stimulation in spite of the pre-existing PD-L1 expression, suggesting that these DCs can induce a strong immune response when given a proper stimulation. This was in line with a study done by Bhattacharya et al [29] where they demonstrated that BM-derived DCs selectively expand regulatory T-cells in the presence of OX40L but not PD-L1. Furthermore, blockade of CD80 on BM-derived DCs has also been shown to discourage regulatory T-cell expansion.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, no marked difference was observed in the relative contents of Treg cells. This seems to be at variance with some earlier observations which have indicated that GM-CSF can support the expansion of Treg cells (22,23), though our present observation may be obscured to a certain degree by the different sizes of the spleens. Other organs displaying pathological changes in the 12B1/GM-CSF/ cl-5-inoculated animals were the livers and the kidneys.…”
Section: Discussioncontrasting
confidence: 56%
“…ICOS is necessary for the development of experimental MG [67], and its inhibition can ameliorate autoimmunity, including in diseases in which autoantibodies are produced [68], suggesting that this may be a useful strategy in MG. Another co-stimulatory molecule induced upon T-cell activation is OX40, which binds to OX40L on the APC and enhances cytokine production, proliferation, and survival of T cells [69]. There is also accumulating evidence that the OX40-OX40L pathway controls the suppressive ability of Tregs [70], and that OX40L expressed on dendritic cells can selectively expand Tregs [71]. Thus, targeting the OX40-OX40L pathway could be further investigated in MG.…”
Section: T-cell Signaling Pathways and Tregsmentioning
confidence: 99%